Late phases [videorecording (DVD)] : night of the lone wolf - Damici, Nick; Embry, Ethan, 1978-; Tina Louise, 1934- (MPI Media Group, 2015)
Blind war veteran Ambrose McKinley has recently moved to Crescent Bay, a seemingly peaceful community on the outskirts of a dense forest. On his first night in his new home, McKinley hears his elderly neighbor attacked by something he's convinced isn't human. When the creature then kills his seeing eye dog, McKinley's thirst for justice turns into a one-man vendetta against the monster that's terrorizing his neighborhood.